The Use of E-learning During COVID-19 Pandemic Era - Mofoluwake Oluwadamilola Uleanya; Gedala Mulliah Naidoo (Athens Institute for Education and Research, 2023)
Communication in teaching and learning space has never been the same following the outbreak of the COVID-19 pandemic. The crisis of COVID-19 has brought about the urgency for most higher education institutions to adopt e-learning. This response was to save the academic year. Hence, this study explores how e-learning has aided African universities to engage their students in teaching and learning. A quantitative research method was adopted for the collection of data. The survey was made up of 400 questionnaires which were randomly administered to the second-and third-year students in the selected South African university. The findings of the study show that e-learning trends before COVID-19 were unappreciated and unaccepted. Meanwhile, following the outbreak of the coronavirus, e-learning has become one of the most sort-out phenomena. However, several factors such as unawareness, lack of funding, and poor internet connectivity, amongst others have always hindered the use of e-learning platforms. Hence, the study recommends amongst others that adequate awareness be made to educate both lecturers and students on the importance and the continuous use of e-learning. Also, funding should be made available for institutions of learning to enable them to adapt to e-learning. The gains achieved must be maintained and continue post-COVID-19.